Controlling the interchain packing and photovoltaic properties via fluorine substitution in terpolymers based on benzo[1, 2-c:4, 5-c']dithiophene-4, 8-dione and benzothiadiazole units. (18th July 2018) - Kini, Gururaj P.; Choi, Jun Young; Jeon, Sung Jae; Suh, Il Soon; Moon, Doo Kyung
Abstract: We present a series of three terpolymers involving benzo [1, 2-c:4, 5-c']dithiophene-4, 8-dione (BDD) and benzothiadiazole (BT) as acceptor units, and oligothiophene as the donor unit (PBDD-TnFBT terpolymers). We optimized the structures of these terpolymers by varying the number of fluorine (F) atoms on the BT unit and studied its effects on photovoltaic performance (P1 (BT), P2 (FBT), and P3 (2FBT)). Density functional theory analysis, optical-electrochemical analysis, and X-ray diffraction study revealed that the fluorination of BT significantly decreased frontier energy levels, enhanced both intermolecular interactions and planarization of polymer backbone in the resulted polymers. As a result, P3, having two F substituents on BT, exhibited stronger intermolecular interactions, predominant face-on orientation with a shorter π-π stacking distance of 3.51 Å, high hole mobility, and optimal nanoscale morphology compared to single F substituent (P2 ) and zero F substituent (P1 ) counterparts. Consequently, polymer solar cells based on P3 demonstrated higher power conversion efficiency (PCE) of 6.2% than those based on P1 and P2 (1.4 and 1.7% respectively). This study illustrates the interrelation between the degree of fluorination and photovoltaic performance and effectively contributes to the design of high-PCE polymer donors for photovoltaic application. Graphical abstract: Image 1 Highlights: Three terpolymers involving BDD and BT with the different number of fluorine (F) atoms were introduced. The interrelation between the degree of fluorination with charge transport behavior and polymer performance in PSC were investigated. Fluorination of BT significantly decreased frontier energy levels and enhanced intermolecular interactions in polymers. The PCE of PSCs was greatly improved from P1 (BT) 1.4% to 6.2 % P3 (2FBT) by the addition of F-atoms.